Recognizing The Notary's Right of Verschoningsrecht to Maintain Confidentiality of Office in Judicial Proceedings - Dantes, Komang Febrinayanti; Ananda Kusuma, Putu Riski (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2025)
find out and analyze the rules in the duties and positions of a Notary regarding the Notary's obligation to maintain the confidentiality of his position. In Article 16 Paragraph (1) letter F of the Notary Office Law Jo. Article 54 of the Notary Office Law states that a Notary has the right of denial. The right of refusal is the right not to speak related to the problem of the deed made by the Notary. The position held by a Notary is a position of trust, as someone who is entrusted, the Notary has rights and obligations, where the right of refusal/verschoningsrecht becomes the right to keep everything that is notified confidential, which is known to him as a Notary even though some are not included in the contents of the deed. The Law on the Position of Notary Number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the Position of Notary gives a right of refusal to a Notary regarding the deeds he made. So the existence of the right of refusal raises juridical problems in the judicial process, where if the Notary is summoned as a witness in the trial, the Notary can use the right of refusal to keep the contents of the deed he made secret.